Descriptor Based QoS Profile in XML - Poon, P.; Dillon, T.; Feng, L.; Chang, Elizabeth (IEEE, 2005)
Many manufacturing processes involve remote control and command process to manage the industrial processes that situated in a disperse locations. For systems which operate in a hectic and distributed environment often involve frequent exchange of information from heterogeneous sources, particularly for those operates on the IP network, it requires the notion of resource indication - quality of service (QoS). Many has proposed the use of XML in such context, however many of the applied approach remains in an ad-hoc fashion and automate integration is not enabled. To provide a better interoperability between distributed industrial informatics systems, we introduce a descriptor based XML definition to feature resources description in distribute control systems with the notion of quality of service. We discuss our XML methodologies used in developing the quality of service for distribute system, and demonstrate an example of telemetry system feature with QoS classes.